PEMBERDAYAAN MASYARAKAT ISLAM BERBASIS KELOMPOK TERNAK (STUDI PENGOLAHAN PUPUK DOTUMAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA TUBANAN JEPARA) - Afidah, Rizki Ainun (Community Development: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to determine firsthand how the process of empowering livestock groups in developing Dotuman organic fertilizer in order to improve the welfare of both Mantra 1 livestock business actors as well as for the people of Tubanan Village. This research uses case study research in the field with a qualitative research approach. Data collection was taken from interviews, observations and documentation. The research informants were 4 people which included companions for the livestock group of the Tanjung Jati B PLTU Corporate Social Responsibility (CSR) program, the Head of the Mantra 1 Group, Members of the Mantra 1 Livestock Group, and the Tubanan Village Community who were involved in managing organic agriculture in Mantra 1 cages.The results of this study indicate that: First, the process of empowering livestock groups in developing Dotuman organic fertilizer has implemented an empowerment process through mentoring activities for empowering livestock groups by forming group organizations, training on modern livestock management and training on livestock waste management. Second, the result of empowering livestock groups in improving community welfare is the application of empowerment through direct action da'wah (bil hal) by providing assistance to underprivileged communities and creating independence, economic sustainability, and fostering welfare in the social and non-formal education fields. Third, constraints in organic management, namely in the field of production to meet market demands that continue to increase but the waste raw materials are limited.